Phytochemical and antioxidant screening of Moringa oleifera for its utilization in the management of hepatic injury - Younis, Noor; Khan, Muhammad Issa; Zahoor, Tahir; Faisal, Muhammad Naeem (Frontiers in Nutrition, 2022)
The present study was designed to investigate the potential of Moringa oleifera against acetaminophen (APAP) induced hepatic injury. Phytochemical and antioxidant potential of extracts (leaves, flowers, and pods) were measured by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and ferric reducing ability of plasma (FRAP). For in-vivo analysis, rats were pre-treated with silymarin (200 mg/kg BW), and M. oleifera leaves (200 mg/kg BW) for 14 days followed by single peritoneal administration of APAP (200 mg/kg i.p.) for 8 hours. Histopathology, biochemical analysis, and gene expression tests were performed on serum, blood, and liver. Pre-treatment with M. oleifera ameliorated organ injury by normalizing the level of liver biomarkers and serum proteins. A low expression level of MAPK-8, TRAF-4, and TRAF-6 genes was observed in the M. oleifera treated group in comparison to positive control (hepatotoxic rats). In conclusion, M. oleifera provides potential therapeutic protection in acute liver toxicity induced by acetaminophen.